Myelodysplastic syndromes - Deeg, H. Joachim (Hematologic Malignancies, 2013)
Myelodysplastic syndromes (MDS) have been studied intensively in recent years and knowledge of the disease process and underlying molecular defects in MDS has expanded rapidly.  With the aging of populations and the concurrent increase in the diagnosis of MDS, these findings are of central clinical importance. New prognostic classification systems with refined prognostic significance have been developed, and molecular abnormalities are now finding their way into the process of clinical decision-making. The book has been  completely updated since the first edition and concisely summarizes the state of the art on all aspects of MDS, including clinical presentation, etiology, epidemiology, molecular biology, classification, and staging. The different chapters provide  guidance on diagnosis and differential diagnosis, as well as on treatment strategies, including the use of hematopoietic growth factors, biology-based treatment, hematopoietic stem cell transplantation, and supportive care. MDS in children is also addressed in a separate chapter. This practically oriented book will be a valuable resource for a broad range of students and practitioners in the field.